2013
DOI: 10.1088/0266-5611/29/10/104003
|View full text |Cite
|
Sign up to set email alerts
|

Applications of elliptic operator theory to the isotropic interior transmission eigenvalue problem

Abstract: The paper concerns the isotropic interior transmission eigenvalue (ITE) problem. This problem is not elliptic, but we show that, using the Dirichlet-to-Neumann map, it can be reduced to an elliptic one. This leads to the discreteness of the spectrum as well as to certain results on possible location of the transmission eigenvalues. If the index of refraction n(x) is real, we get a result on the existence of infinitely many positive ITEs and the Weyl type lower bound on its counting function. All the results ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 26 publications
2
85
0
1
Order By: Relevance
“…The problems (B) and (C) are more difficult, and they are of some interest for the numerical analysis of the (ITEs). In this direction it is interesting to find an optimal eigenvalue-free region and a Weyl formula with optimal remainder (see [12], [5], [13], [8] and the references therein). In a recent work [15] the authors showed that (B) and (C) are closely related each other, and a larger eigenvalue-free region leads to a Weyl asymptotics with a smaller remainder term.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…The problems (B) and (C) are more difficult, and they are of some interest for the numerical analysis of the (ITEs). In this direction it is interesting to find an optimal eigenvalue-free region and a Weyl formula with optimal remainder (see [12], [5], [13], [8] and the references therein). In a recent work [15] the authors showed that (B) and (C) are closely related each other, and a larger eigenvalue-free region leads to a Weyl asymptotics with a smaller remainder term.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…In the isotropic case the eigenvalue-free region (2.5) has been also obtained in [14] when the dimension is one. In the general case of arbitrary domains transmission eigenvalue-free regions have been previously proved in [5], [6] and [12] (isotropic case), [15] and [16] (both cases). For example, it has been proved in [15] that, under the conditions (2.2) and (2.4), there are no transmission eigenvalues in λ ∈ C : Re λ > 1, |Im λ| ≥ C ε (Re λ) 1 2 +ε , C ε > 0, for every 0 < ε ≪ 1.…”
Section: Applications To the Transmission Eigenvaluesmentioning
confidence: 88%
“…The direct substitution of the values of (25) and (29) into (23) and (24) shows that one always has v ∈ H 1 (B re,R ), while the condition v ∈ L 2 (B r i ,re ) appears to be equivalent to (11), so it holds for any h for a ≥ r 2 e /r i as before, otherwise a very strong regularity of h is required.…”
mentioning
confidence: 88%